Meningkatan Motivasi Belajar Menggunakan Model Pembelajaran Picture And Picture pada Mata Pelajaran Ilmu Pengetahuan Alam - Laili Rahmi; Delya Yuswanti (Jurnal Dharma PGSD, 2021)
Science learning that is not effectively by the teacher will affects the low learning motivation students. This is related to the results of observations at MIS Nailul Ikhsan Sungai Arang, Bungo city Jambi which students show are less active in learning and their lack of attention to teacher explanations. The measurement of initial motivation using the observation instrument of motivation also shows that the average percentage of achievement of the students' motivation indicators is only 39.8 which is in the "moderately motivated" category. If this situation is not resolved, it will result in not achieving the learning objectives. Therefore, the researcher proposes a solution by applying the picture and picture learning model which aims to increase student motivation, especially in science subjects. The research method used was classroom action research using the Kemmis-Taggart model with the stages of planning, action and observation, reflection and re-planning. In the first cycle research results obtained an average increase in the percentage of student learning motivation, namely 70.8 which means that in the "motivated" category. The research was continued until cycle II and obtained an average percentage of 89.7 which means that it has reached the highest category, namely "highly motivated". Based on this, it can be concluded that the application of the picture and picture learning model in science learning can increase student learning motivation.